O filme Pixote, a lei do mais fraco e o governo das Crianças marginalizadas (1980-1985) - Pereira Junior, Luis Alberto (2014)
The matter and source of this research is the cinematographic work Pixote, a lei do mais fraco, produced by the Argentine director Hector Babenco. The official casting of this work was in 1980 during the final stage of the Brazilian military dictatorship (1964-1985), in the period of (re)-democratization. The research attempts to demonstrate how the government practices, control and disciplinarization of the categorized marginal childhood occurred in the reformatory school and in Brazilian big cities. The movie scenes, journalistic reports of printing press and expert‟s report of military censorship, produced when the film was originated and exhibited, allowed us to enter the historical meanders of that context and also to better understand the conditions, power relationships and counter-power which reached the little unfortunate kids‟ lives in Brazil. Theoretical and methodological references which subsidized and guided the analyses were based on categories and notions of Foucault‟s thoughts, and it significantly aided to better understand social practices destined to the subjectification of this social category. Not only the understanding of power practices on the marginalized childhood was provided through this research, but it was also possible to perceive the strategic use of those entities in order to set up repressing and disciplinary mechanisms, such as judicial, police, discursive and pedagogical mechanisms extensible to the entire social corpus, cooperating to become the attempts of controlling childish populations more efficiently. It was possible through the sources to understand that representations and identities of the so-called minor transgressors, reflected in large scale in the press, aided to reassert and (re)-signify the ideation and conceiving of minor transgressors. Finally, we defend that the movie Pixote and the printing press reports work as pedagogical mechanisms, supporting the establishment of abnormality and normality standards, since in a binary system the ugly helps to compose what is beautiful; the undesirable, what is desirable; and the bad, what is good, as well as interdependent patterns.